Epicardial Transplantation of Adipose Mesenchymal Stromal Cell Sheets Promotes Epicardial Activation and Stimulates Angiogenesis in Myocardial Infarction (Experimental Study) - Konstantin V. Dergilev; Zoya I. Tsokolaeva; Irina B. Beloglazova; Anastasia V. Komova; Sofia V. Pavlova; Dmitry O. Traktuev; Yelena V. Parfyonova (Общая реаниматология, 2019)
Aim: to evaluate the impact of tissue-engineered structures (TES) transplantation based on mesenchymal stromal cell (MSC) sheets in myocardial infarction on the activation of the epicardial cell pool and vascularization of the damaged zone.Materials and methods. Mesenchymal stromal cells were obtained from samples of subcutaneous fat of Wistar rats and C57Bl/6 mice. Tissue engineering structures were obtained by culturing cell sheets on thermosensitive plates (Nunc Dishes with UpCell Surface). Transplantation of TESs was performed after myocardial infarction modeling in rats by ligation of the anterior descending coronary artery. Transplant cells and damaged zones were assessed using immunofluorescent staining of myocardial cryosections. The impact of MSC secretion products on the migration activity of epicardial cells in vitro was evaluated using the explant culture method.Results. MSCs in TESs after transplantation remain viable and induce activation of the epicardial cell pool and local increase of the damaged zone vascularization. The in vitro experiments showed that the conditioned environment of MSCs stimulates the migratory activity of epicardial cells and initiates the formation of activated Wt1/POD1 precursor cells.Conclusion. TES transplantation on the basis of MSC sheets seems to be a promising approach for effective delivery of viable cells into myocardium to activate the epicardial cellular niche and reparative angiogenesis.